2012
DOI: 10.1118/1.3679340
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization of intensity modulated proton therapy

Abstract: The authors find that the worst-case robust optimization provides robust target coverage without sacrificing, and possibly even improving, the sparing of normal tissues. Our results demonstrate the importance of robust optimization. The authors assert that all IMPT plans should be robustly optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
395
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 312 publications
(399 citation statements)
references
References 23 publications
3
395
1
Order By: Relevance
“…Instead of attempting to improve the optimization algorithm of the TPS, which is clearly out of the control of a user, the proposed platform and the use of an out‐of‐the‐TPS decision function here allows us to imitate a planner's interactive planning process to search for the optimal solution that would otherwise require much more manual effort. The approach is quite general and should be applicable to facilitate the treatment planning of other modalities such as brachytherapy, (37) proton therapy, 38 , 39 station parameter optimized radiation therapy (SPORT), 29 , 40 gamma knife, (41) breast planning (42) or similar.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of attempting to improve the optimization algorithm of the TPS, which is clearly out of the control of a user, the proposed platform and the use of an out‐of‐the‐TPS decision function here allows us to imitate a planner's interactive planning process to search for the optimal solution that would otherwise require much more manual effort. The approach is quite general and should be applicable to facilitate the treatment planning of other modalities such as brachytherapy, (37) proton therapy, 38 , 39 station parameter optimized radiation therapy (SPORT), 29 , 40 gamma knife, (41) breast planning (42) or similar.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the extent of rectal displacement (≥ 9 mm) was significant enough for both field arrangements to observe similar benefits of the rectal spacers to reduce the volume receiving high dose to the rectum. Consequently, while there are some potential benefits of using anterior proton beams without a rectal spacer, LAT fields should be preferred with a rectal spacer especially because they are also more robust 25, 38. A rectal spacer may also be especially beneficial for prostate cancer patients with a hip prosthesis who receive proton therapy as an anterior beam is commonly used to avoid treating through the prosthesis, and the LAO/RAO configuration would then be preferred in such situations 39…”
Section: Discussionmentioning
confidence: 99%
“…In the cancer literature, examples of analogous efforts for designing robust treatment protocols can be found in radiotherapy (51)(52)(53)(54). The challenges in designing a robust radiation treatment protocol can largely be attributed to geometric uncertainty and interpatient variability (54).…”
Section: Discussionmentioning
confidence: 99%
“…For the same beam arrangement, they computed a different dose distribution accounting for these uncertainties and compared this to the optimal dose distribution. They applied this approach to the lung, skull base and prostate and found that compared with IMPT plans optimized using conventional (nonrobust) methods, their method resulted in radiotherapy plans that are less sensitive to beamlet range and setup uncertainties (52). In a series of papers, robust optimization was used for planning intensity modulated radiation therapy for lung cancer in the face of uncertainty caused by breathing (51,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation